MEMAHAMI PERTALIAN DESA PAKRAMAN DI BALI DENGAN KARANG AYAHAN SEBAGAI BAGIAN DARI PALEMAHAN BERDASARKAN KONSEP TRI HITA KARANA - Wiguna, Made Oka Cahyadi (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2018)
Desa Pakraman in Bali is included in the category of territorial customary law community and at the same time religious customary law community. On that basis, it should be understood that actually desa pakraman has autonomy in regulating the order of life and social life of its members. The existence of desa pakraman in Bali is very much needed for its members, as an institution that has the authority to regulate the life arrangements of indigenous law communities, including regulating, management, designation, maintenance and preservation of karang ayahan as the customary land of desa pakraman. The existence of karang ayahan is very dependent on the existence of a desa pakraman. Mastery of karang ayahan by krama desa who has the right, is used as a place of residence or other interests with the obligation to pay attention to certain general provisions set by desa pakraman in awig-awig and perarem. Besides that, the karang ayahan is also an integral part of the territory or wewengkon of a desa pakraman. For village people, the area is an important part of sovereignty from a desa pakraman that must be maintained. Keywords: the existence of desa pakraman, the function of the karang ayahan